Field Data Analysis of a Flooding Household Stormwater Detention System - Ngu, J.O.K.; Mah, D.Y.S.; Taib, S.N.L.; Mannan, Mohammad Abdul; Hoo, T.Y. (World Researchers Association, 2021)
This study describes the analysis being carried out for a field test of household stormwater detention system. The set up included a 0.95m2 house roof and a 4.40m x 4.70m x 0.45m on-site detention tank. Roof gutter and 0.1m diameter downpipe were installed connecting the roof to tank while 0.05m diameter pipe was connected to the tank as outlet. A total of 114 full units and 12 half units of precast concrete pieces named StormPav Green Pavement were laid within the tank. Two observed events are highlighted. Storm event happened on 22 February 2020 with a 48mm peak rainfall causing a flash flood within the housing estate of the field test site. Another storm event on 16 January 2020 had a 42mm peak rainfall but no flooding occured. Both observed storm events were classified as heavy storms for having rainfall depth over 40mm.